Can resistance to either isoniazid or rifampicin predict multidrug resistance tuberculosis (MDR-TB) - Mchaki, Betty R. (2023)
Previous studies have shown significant differences and lack clarity on whether resistance to either isoniazid or rifampicin can predict multidrug resistance tuberculosis (MDR-TB). Some consider rifampicin resistance to be a surrogate for MDR-TB. We, therefore, conducted this study to determine resistance to either isoniazid or rifampicin can predict MDR-TB.